An Epidemiological Survey of Work-Related Musculoskeletal Disorders among Welders in a Conflict-Recovery Region: In North-Eastern, Nigeria - Suleiman Mohammed; Mannir Kassim; Hamza Sabo Muhammad; Bishir Sabo; Usman Gidado (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2026)
Welding is an arduous occupation characterized by repetitive tasks, prolonged awkward postures, and substantial biomechanical strain. In the conflict-recovery context of North-Eastern Nigeria, the absence of ergonomic regulation within the informal sector may further increase the risk of work-related musculoskeletal disorders (WRMSDs). This study aims to evaluate the prevalence, anatomical distribution, and functional disability associated with WRMSDs among welders in Maiduguri, Borno State, Nigeria. A cross-sectional descriptive survey was conducted among 306 welders using a modified Standardized Nordic Musculoskeletal Questionnaire. Data were collected on socio-demographic characteristics, 12-month period prevalence, 7-day point prevalence, and work-related disability. Data were analyzed using descriptive statistics and chi-square analysis, with statistical significance set at p < .05. The findings show that most participants were aged 33–37 years (33.3%) and had an occupational tenure of 2–12 years (53.9%). The axial skeleton emerged as the primary site of morbidity, with a 12-month prevalence of 31.6% for the lower back and 31.0% for the neck. A severity paradox was identified in the lumbar region, where the reported disability rate (34.3%) exceeded the overall period prevalence, suggesting that most lumbar injuries in this cohort progressed to total functional impairment. High 7-day point prevalence was also observed for both the neck (31.6%) and lower back (31.3%), indicating chronic and persistent morbidity. No statistically significant associations were found between demographic variables and WRMSD occurrence, p > .05. The study concludes that welders in North-Eastern Nigeria experience a substantial burden of chronic spinal stress, with the lower back serving as the leading source of occupational disability. This study contributes to occupational health research by highlighting the rapid transition from musculoskeletal discomfort to functional impairment in informal welding work. The findings imply the need for targeted ergonomic interventions, community-based occupational physiotherapy, and workplace modifications to protect the physical health and productivity of this essential workforce during regional economic reconstruction.